A 1995 conversation with John A. Pople (1925 − 2004) - Hargittai, Istvan (Structural chemistry, 2025)
The Møller-Plesset theory, which originated in the 1930s is being widely used to include electron correlation in ab initio molecular orbital calculations. The essence of the density functional theory is to try to use the density distribution of electrons, the same thing which you measure in X-ray crystallography. In electronic structure theory, you study the distribution of the electrons for a particular nuclear arrangement in the molecule, work out the energy at that nuclear arrangement and then explore different nuclear arrangements. The density functional theory says that if you knew exactly the electron density distribution of the molecule for a given nuclear position, then you should be able to deduce from that the total energy of the molecule.